A Risk Communication Strategy to Support Implementation Child Rights Protection Program: A Descriptive Qualitative Study in ALIT Indonesia Foundation during the COVID-19 Pandemic - Amalia Fibrianty; Rachmat Kriyantono; Maulina Pia Wulandari (International Journal of Science and Society, 2021)
During the pandemic COVID-19, the number of Child Rights violations have been increased such as sexual harassment, the exploitation of the children, and child abuse. Moreover, during the regulation such as “lockdown” that forced people to stay at home has been putting the children into another risks. Thus, it is important for Civil Society Organization (CSO) who works with the children to have its risk communication strategy in its Child Rights Protection (CRP) program implementation. This study is to address the risk communication and community engagement (RCCE) strategy in supporting the sustainability of CRP program implementation in ALIT Indonesia Foundation during pandemic COVID-19. The writer assumed that the organization has been applied a good strategy for its risk management. Moreover, using a descriptive qualitative research methods and data gathering from interview and literature review, it founds that the risk communication strategy adjustment applied by ALIT Indonesia Foundation on its CRP program implementation not only helped the organization in working with the children and their family as the target group, but also giving advocacy about the Child Rights to the stakeholders during pandemic COVID-19. The organization run some strategies based on the government’s health protocols during pandemic, such as physical distancing, wearing mask, hand washing. They also use social media such as Zoom, WhatsApp, Facebook, Instagram and YouTube to outreach their target group who live in the internet-accessible area, but for those who are living in the remote area, they had field staffs as the interconnector to their volunteer in the field, and spread the key messages of the CRP program through local radio station, or they gather the children of 4 who live nearby to disseminate the information.